RECONSTRUCTION OF ISLAMIC TAMADUN IN MODERN TIMES (DA’WAH APPROACH) - mastori mastori (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2022)
Tamadun Islam once reached its peak in a long period of time on earth, both in the fields of science, economics, politics and law. The triumph of Islamic civilization gave a great contribution to the emergence of western civilization which has been trapped for so long on the dominance of church power that limits academic freedom and scientific findings. Having managed to rise from adversity, the west then rose and became a major competitor for the Islamic civilization. finally, the Islamic civilization through the crusade and the war of thought they succeeded in winning by subverting Islamic power in the Ottoman Turks in 1924. After the fall of Islamic civilization, Muslims lost their power and authority. The greatness possessed by Islam gradually began to be replaced by secular western civilization. This study discusses how to reconstruct the Islamic civilization which has been destroyed from its place as the center of world civilization with a da'wah approach and thought. By using the approach of political analysis and da'wah this study shows that: first, da'wah rebuilding Islamic civilization must be done in congregation or collectively. Second, the nature of the struggle must not neglect the political aspects which in fact are the guardians of Islamic civilization. third, the da'wah approach that must be taken does not use violence and intimidation but through changes in Islamic thought to touch the substantial aspects of Islamic thought, namely aqidah, sharia and moralsKeyword: Tamadun, Da'wah, Reconstruction